Identity and Epistemic Emotions During Knowledge Revision: A Potential Account for the Backfire Effect. Issue 5 (3rd July 2016) - Trevors, Gregory J.; Muis, Krista R.; Pekrun, Reinhard; Sinatra, Gale M.; Winne, Philip H.
Abstract : Recent research has shown that for some topics, messages to refute and revise misconceptions may backfire. The current research offers one possible account for this backfire effect (i.e., the ironic strengthening of belief in erroneous information after an attempted refutation) from an educational psychology perspective and examines whether emotions mediate the relationship between self-concept and learning from refutation texts. In an experimental design, 120 undergraduate students responded to a questionnaire focused on their dietary self-concept and were randomly assigned to read an expository or refutation text on the topic of genetically modified foods. Immediately after reading, participants self-reported their emotions followed by completing post-test measures of their knowledge and attitudes of the topic. Results showed an interaction between self-concept and text condition on emotions wherein self-concept predicted negative emotions (i.e., confusion, anxiety, frustration) while reading a refutation text specifically. Further, negative emotions significantly mediated relations between self-concept and post-test knowledge and attitudes. Implications for educational design and future research are discussed.